2020
DOI: 10.21203/rs.3.rs-32034/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulatory network underlying alterations of gene expression in early death of Huntington's disease

Abstract: The aim of this study is to explore the genomic mechanism of early death in Huntington’s disease (HD). We identified 10160 and 1511 differentially expressed genes (DEGs) from comparisons of HD versus control and early versus late death, respectively. On the basis of 922 overlapped DEGs among them, six functional modules were established by weight gene correlation network analysis. The turquoise module most strongly related to overall survival of HD was significantly enriched in GABAergic synapse, retrograde en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The GNB5 which encodes the beta 5 subunit of heterotrimeric G proteins, is predominantly expressed in the nervous system and is essential for natural brain development [ 36 , 37 ]. One study showed that GNB5 is a hub gene in Huntington's disease (HD) [ 38 ]. Utpala et al demonstrated that GNB5 is one of the 10 most significant hub genes involved in GABAergic synapse, Retrograde endocannabinoid signaling, and Ras signaling pathways in AD (Alzheimer disease) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GNB5 which encodes the beta 5 subunit of heterotrimeric G proteins, is predominantly expressed in the nervous system and is essential for natural brain development [ 36 , 37 ]. One study showed that GNB5 is a hub gene in Huntington's disease (HD) [ 38 ]. Utpala et al demonstrated that GNB5 is one of the 10 most significant hub genes involved in GABAergic synapse, Retrograde endocannabinoid signaling, and Ras signaling pathways in AD (Alzheimer disease) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%